Integrating Moral Values in Classroom Management: Strategies for Enhancing Discipline among Students of Pagatpat Elementary School - Mara, Joann T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the role of teachers in incorporating moral values within classroom management strategies in the Division of Zambales, specifically in Zone I. The research focuses on the de-mographic profile of teachers, their practices in integrating moral values into classroom discipline, and the challenges they face. A total of 11 teachers participated, providing insights into their sex, age, length of service, positions, and highest educational attain-ment. The study explored how teachers implement moral values through strategies such as establishing classroom rules, modeling behavior, building student relationships, and integrating moral lessons into the curriculum. Additionally, the study identifies the challenges teachers face, including diverse student backgrounds, limited time for moral education, and lack of support or resources. The findings reveal that while teachers are committed to integrat-ing moral values, challenges such as curriculum constraints and insufficient resources hinder the full implementation of moral ed-ucation in the classroom. The study concludes with recommenda-tions for professional development, curriculum enhancement, and increased resource allocation to support teachers in promoting moral values and discipline in schools.